VENDOR SELECTION AND DETERMINING PROCUREMENT QUOTAS IN CONDITIONS WHEN DISCOUNTS ARE OFFERED ON THE TOTAL VALUE OF THE CONTRACTED PROCUREMENT OF MANY DIFFERENT PRODUCTS - Zoran Babić; Tunjo Perić; Sead Rešić (Human Research in Rehabilitation, 2012)
Vendor selection is a very significant business problem for ensuring the competitiveness on the market. That is why companies pay great attention to this problem. To solve the vendor selection problems can be applied to a number of quantitative methods. Depending on the goals of the company the vendor selection can be a mono-criterion or multi-criterion programming problem. This paper deals with the problem of vendor selection and determining procurement quotas from selected vendors under conditions where vendors offer discounts to the total order value within a specified period where the buyer buys more products from the vendors. The total value of procurement costs in a given period is taken as an optimization criterion. In this paper the specific flour purchase problem is solved for a company that manufactures bakery products.